An Analysis of Translating Procedures In Iphone Start Up Guide Book - Manda Negara, Irma; Nurbaiti, Ida (LPPM STBA Pontianak, 2017)
This research aims to identify translation prodecures and methods used by the translator in translating iphone 5 start up guide book from English as source language into Indonesia as target language. Qualitative descriptive was employed to analyse the data by referring the theories proposed by Newmark. The result of data analysis shows that there are six translation procedures found in the text: transposition (126 items or 21%), modulation (91 items or 15%), borrowing (164 items or 27%), calque (60 items or 10%), equivalence (87 items or 15%) and reduction (72 items or 12%). Whereas for the methods that used by the translator are 233 items or 39% using literal, faithful (146 items or 24%), adaption (144 items or 24%), communicative (77 items or 13%).